2009
DOI: 10.1116/1.3274061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Matrigel interfaces during defined human embryonic stem cell culture

Abstract: Differences in attachment, proliferation, and differentiation were measured for human embryonic stem (hES) cells cultured on various substrata coated with Matrigeltm, a blend of extracellular matrix proteins derived from murine tumor cells. The authors observed that hES cells attach and grow poorly on Matrigel adsorbed onto polystyrene, while they proliferate when exposed to Matrigel adsorbed onto glass or oxygen plasma treated polystyrene (e.g., “tissue culture” treated polystyrene). Furthermore, hES cells gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…In this study we cultured GMSCs within MatrigelBD, the scaffold allowed cellular proliferation and preserved the typical morphological features of the cells. Our results are consistent with those reported by Kohen et al (2009), who demonstrated that cells grown on MatrigelBD retained all pluripotent stem cells features. Similar results reported by Chan et al (2011) demonstrated the biocompatibility of Puramatrix TM with DPSCs and SHEDs, showing that this hydrogel is compatible and allows cellular proliferation (Drury & Mooney; Chan et al).…”
Section: Discussionsupporting
confidence: 83%
“…In this study we cultured GMSCs within MatrigelBD, the scaffold allowed cellular proliferation and preserved the typical morphological features of the cells. Our results are consistent with those reported by Kohen et al (2009), who demonstrated that cells grown on MatrigelBD retained all pluripotent stem cells features. Similar results reported by Chan et al (2011) demonstrated the biocompatibility of Puramatrix TM with DPSCs and SHEDs, showing that this hydrogel is compatible and allows cellular proliferation (Drury & Mooney; Chan et al).…”
Section: Discussionsupporting
confidence: 83%
“…The WCA for TCPS was about 51°, which is consistent with prior reports [11]. For the prepared samples in this study, the WCAs for all of the nanofibours scaffolds were higher than those of TCPS, indicating that the scaffolds were hydrophobic.…”
Section: Figuresupporting
confidence: 80%
“…When the topography of the biologically derived ECM material Matrigel was changed owing to adsorption onto different surfaces this affected both attachment and proliferation of hES cells (Kohen et al, 2010). The importance of surface topography for attachment was further emphasised by the finding that mES cells were not able to adhere to a planar polyamide surface in contrast to a fibrillar surface of the same material (Nur-E-Kamal et al, 2006).…”
Section: Attachment and Proliferationmentioning
confidence: 97%